2D controlled source electromagnetic modeling in layered medium using hybrid method - Hussain, N. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents a hybrid numerical solution of field governing equations of electromagnetic (EM) geophysical method. The proposed method take advantage of implementation simplicity of finite difference (FD) method and the advantage of multiscale resolution of wavelet transform. For evaluation of the proposed method, 2D hypothetical geoelectrical layered-model with simple anisotropy regions are assumed for geophysical modeling. The FD method employed staggered grid scheme, which gives electric field responses on uniform rectangular meshes. Results generated from FD methods give coarse solution of electric field responses. To further refined the electric field value, wavelet expansion is used which produce a better solution that indicates the presence of thin or thick hydrocarbon in the model. © 2016 IEEE.